Unraveling the mechanism of fragrance release in Cestrum nocturnum through transcriptome and volatile compound profiling - Sitong Qiao; Anqi Ding; Tao Liu; Hangcheng Hu; Mengting Li; Jiyang Wang; Leixing Deng; Shiheng Lyu (Scientific Reports)
Abstract Cestrum nocturnum is a plant that blooms and emits fragrance at night but the mechanism behind its fragrance release remains poorly understood. Here, the floral substances and differential regulatory genes in the petals of C. nocturnum at night were explored by HS-SPME-GC/MS and transcriptome sequencing. Benzaldehyde, phenyl acetaldehyde and benzyl acetate were identified as the main floral scent substances involved in the phenylpropanoid biosynthesis pathway of C. nocturnum. The DEGs in this pathway, PALs, PAAS, PARs, 4CLs, CFATs, BEAT, EGSs and BAMT, showed high expression levels during flowering. Additionally, these genes may play an important role in the formation of a regulatory network for floral scent substance synthesis. DEGs in day/night alternates and plant hormone signalling pathways also had important functions in flowering and fragrance release. These included CO, FT and genes related to the promotion of phytohormone (GA, ABA, IAA, BR) biosynthetic and signal transduction, which showed high expression levels during flowering. These results provide a theoretical reference for the expression levels of differentially expressed functional genes in the flowering and fragrance release of C. nocturnum and lay a foundation for further research on night-blooming aromatic flowers.